AB0154 Role of Pro-Inflammatory Cytokines in The Endoplasmic Reticulum Associated-Protein Degradation in Sjögren's Syndrome Patients. (15th July 2016) - Barrera, M.-J.; Aguilera, S.; Castro, I.; Cortés, J.; Bahamondes, V.; Urzúa, U.; González, S.; Molina, C.; Leyton, C.; González, M.-J.
Abstract : Background: Due to its high secretory activity and the complexity of synthesized secretory products, salivary gland (SG) acinar cells are susceptible to endoplasmic reticulum (ER) stress under physiological conditions. ER stress triggers a mechanism known as the "Unfolded Protein Response" (UPR) aiming to restore ER homeostasis. Various ER stress-related disorders have been described in SG of Sjögren's syndrome (SS) patients, including intracellular accumulation of mucins (1) and dilated ER cisternae (2). Also, high levels of pro-inflammatory cytokines present in SG of SS-patients may act as local ER stressors and may play an important role in ER stress induction and perpetuation (chronicity). Previous results from our laboratory indicate a decreased activation of the IRE1α/XBP-1s pathway of the UPR (unpublished data) indicating a chronic ER stress condition. Despite this, the SG acinar cells from SS-patients have low levels of apoptosis (3), suggesting that alternative UPR pathways such as ATF6α could be activated. ATF6α pathway promotes survival mechanisms such as ER-associated protein degradation (ERAD), which has been found hyper-activated in arthritis rheumatoid (4). Objectives: To determine the expression and localization of ATF6α pathway components and molecules participating in ERAD in labial SG (LSG) of SS-patients. The effect of pro-inflammatory cytokines on both ERAD and cell survival was also studied using LSG extracts of SS patients and a three-dimensional (3D) acini model. Methods: Expression of ATF6α, ERAD-components, pro-inflammatory cytokines, cIAP2 and cleaved-caspase-3 were determined in SG of SS-patients and controls by Western-blot and qPCR. Localization of selected molecules was evaluated by immunofluorescence. Correlation between cytokines and ERAD-components was analyzed with the Pearson's test. ATF6α and ERAD activation, pro- and anti-apoptotic markers and cell viability were determined in a 3D HSG cell culture system treated with cytokines. Results: LSG of SS-patients showed high cytokines levels and high activities of ATF6α and ERAD pathways. No significant differences in cleaved-caspase-3 and cIAP2 levels between both groups were observed. Significant positive correlations were observed between pro-inflammatory cytokines and ERAD-components expression levels. These correlations were demonstrated in in vitro 3D cell cultures treated with TNF-α and/or IFN-γ for prolonged times, without increased apoptosis. Conclusions: In SS-patients, the permanent action of pro-inflammatory cytokines establishes a chronic ER stress condition with ATF6α pathway activation and increased ERAD mechanism. Higher ATF6α pathway levels would increase ERAD activity, which may help to control chronic ER stress and prevent death by apoptosis. References: Arthritis Rheum. 2011;63:3126–35. Arthritis Rheum. 2003;48:2573–84. Lab Invest. 2001, 81:95–105. Arthritis Res Ther. 2005;7:181–6. Acknowledgement: Fondecyt 1120062 (MJG, SA, CM, SG) and PhD fellowship Conicyt-Chile (MJB, JC). Disclosure of Interest: None declared